Superleague case: Commentary of the judgment of the court of 21 december 2023, c-333/21 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In the judgment in question, the CJEU answers the questions referred for a preliminary ruling by the 17th Commercial Court of Madrid in the case brought by the Superliga against FIFA and UEFA. Those questions concern whether the decision of those two bodies not to authorise the holding of the Superliga in their markets of activity infringes competition rules and European freedoms. The Court concludes that it does. It states that, in relation to the competition rules, which are the subject of this study, this conduct by FIFA and UEFA constitutes an abuse of the dominant position held by these companies by preventing new competitors from entering the market (art. 102 TFEU) and, furthermore, as associations of undertakings, their conduct is harmful to competition and cannot be exempted from the sanction, inter alia, for eliminating competition on the market (art. 101 TFEU).